Mechanics of Soccer Heading and Protective Headgear - Mohd Hasnun Ariff, Hassan; Zahari, Taha; Iskandar, Hasanuddin; Mohd Jamil Mohamed, Mokhtarudin (Springer, 2018)
This short book provides a concise study of the mechanics of head impact in a soccer heading manoeuvre. It describes the development and validation of finite element models of soccer ball and human head, as well as the simulation of brain dynamics after ball-to-head impact. In addition, it also presents a computational study of the efficacy of wearing protective headgear in mitigating the risk of concussion due to heading in soccer.